Fast microbubble dwell-time based ultrasonic molecular imaging approach for quantification and monitoring of angiogenesis in cancer - Pysz, Marybeth A.; Guracar, Ismayil; Tian, Lu; Willmann, Jürgen K. (Quantitative Imaging in Medicine and Surgery, 2012)
Purpose: To develop and test a fast ultrasonic molecular imaging technique for quantification and monitoring of angiogenesis in cancer. Materials and methods: A new software algorithm measuring the dwell time of contrast microbubbles in near real-time (henceforth, fast method) was developed and integrated in a clinical ultrasound system. In vivo quantification and monitoring of tumor angiogenesis during anti-VEGF antibody therapy was performed in human colon cancer xenografts in mice (n=20) using the new fast method following administration of vascular endothelial growth factor receptor 2 (VEGFR2)-targeted contrast microbubbles. Imaging results were compared with a traditional destruction/replenishment approach (henceforth, traditional method) in an intra-animal comparison. Results: There was excellent correlation (R2=0.93; P